Cyphos IL 102 assisted liquid-liquid extraction studies and recovery of vanadium from spent catalyst. (November 2018) - Singh, Rashmi; Mahandra, Harshit; Gupta, Bina
Graphical abstract: Highlights: Cyphos IL102 explored for the first time for extraction and recovery of V(V). Extraction via anion exchange mechanism involving V10 O26 (OH)2 4− species. Separation of V from associated metal ions with high separation factor. 99.8% V recovered from spent catalyst as pure V2 O5 using simple stripping agent. Advantage – No phase modifier required, high loading, recycling power of extractant. Abstract: In this study, Cyphos IL 102 (trihexyl(tetradecyl)phosphonium bromide) diluted in toluene has been explored as an organic phase for the extraction, separation and recovery of V(V) from sulphate medium. The influence of different fundamental extraction variables namely acids and extractant concentration, equilibration time and temperature on the V(V) extraction has been evaluated. Different stripping agents have been studied for back extraction of vanadium. Saturation and recycling capacity of the extractant has also been performed. Partition behavior of other associated metal ions namely Mn(II), Fe(II/III), Al(III), Cr(III), Ti(IV), Mo(VI) and W(VI) were carried out. The extraction data offer conditions for the binary separation of V(V) from associated metal ions with high separation factors. Optimized parameters have been employed for the extraction and recovery of V(V) from spent V2 O5 catalyst leach liquor. To find out the number of stages required to achieve quantitative extraction/stripping of vanadium, McCabe-Thiele plots were drawn, which were further verified by counter current simulation studies. In addition, vanadium oxide was synthesised using thermal decomposition and characterized by XRD, FESEM and EDX techniques.